Robust feedback control design using PSO-based optimisation: a case study in gantry crane control - Solihin, Mahmud Iwan; Akmeliawati, Rini; Legowo, Ari (Inderscience, 2011)
In this paper, a robust state feedback control design using particle swarm optimisation-based constrained optimisation The feedback controller is designed based on state space model of the plant with structured uncertainty such that the closed-loop system would have maximum stability radius. A wedge region is assigned as a constraint to locate desired closed loop poles. The proposed method is applied into design of anti-swing control of an automatic gantry crane experiment. A comparison with that of LQR-based controller is made. The result shows that the proposed method effectively locates the closed loop poles within the prescribed wedge region and its robust performance is guaranteed.